Association between age at menarche and the risk of myopia at the age of 15 in Chongqing, China: a cross-sectional study - Jing Zhang; Ruili Li; Yong Zhang; Tian OuYang; Dan Ao; LiYan Gong; Li He; Xiaoya Qi; Xiyuan Zhou (Frontiers in Medicine)
IntroductionMenarche is one of the important indicators of girls’ physical, nutritional, and reproductive health. This study aims to identify the relationship between the age at menarche and the risk of myopia at the age of 15.MethodsGirls aged 15 were recruited when they visited the hospital for physical examination required for enrollment in the high school. Eligible participants underwent anthropometric measurements and an ocular examination, and they completed a questionnaire to gather personal information, including age at menarche. Ocular indexes were compared across early, normal, and late menarche groups, and multivariate regression was performed to analyze the relationships between age at menarche and myopia.ResultsAmong the 376 participants around the age of 15, 115 girls were classified into the early menarche group, 185 into the normal menarche group, and 76 into the late menarche group. The prevalence of myopia was 95.7, 87.6, and 86.6% for the right eye (p = 0.048) and 89.6, 77.8, and 68.4% (p = 0.001) for the left eye in the early, middle, and late menarche groups, respectively. Age at menarche was negatively and significantly associated with myopia, particularly with moderate to severe myopia in 15-year-old girls (p = 0.039 for the right eye, p = 0.001 for the left eye).DiscussionAge at menarche, as a marker of the onset of puberty, was identified as an independent risk factor of myopia in teenage girls, particularly for moderate to severe myopia. This implies that accelerated physical development during puberty may contribute to the onset and progression of myopia in the context of modern lifestyles in urban China. Additional interventions should be considered for this subgroup of children.